2014
DOI: 10.11607/ijp.3807
|View full text |Cite
|
Sign up to set email alerts
|

Technical Complications and Failures of Zirconia-Based Prostheses Supported by Implants Followed Up to 7 Years: A Case Series

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 0 publications
1
24
0
1
Order By: Relevance
“…Three-unit FDPs also presented a survival rate similar to conventional FDPs [5] after 10 years. In a seven-year study, Kolgeci and co-workers observed that Y-TZP-based prostheses are clinically successful on dental implants as well [12]. This was corroborated by another 10-year clinical study [13].…”
Section: Introductionmentioning
confidence: 80%
“…Three-unit FDPs also presented a survival rate similar to conventional FDPs [5] after 10 years. In a seven-year study, Kolgeci and co-workers observed that Y-TZP-based prostheses are clinically successful on dental implants as well [12]. This was corroborated by another 10-year clinical study [13].…”
Section: Introductionmentioning
confidence: 80%
“…The studies were grouped into studies reporting results on CAD/CAM-fabricated implant-supported single crowns (SCs), CAD/CAM-fabricated implant-supported partial fixed dental prostheses (FDPs), and CAD/CAM-fabricated implant-supported fixed dental full-arch prostheses (full-arch FDPs). If there were any uncertainties regarding the reported study materials, authors or coauthors were contacted (Pozzi et al 2012(Pozzi et al , 2013aWeinstein et al 2012;Katsoulis et al 2013;Kolgeci et al 2014;Lopes et al 2014;Worni et al 2014). The two investigators selected potential studies and after consensus the studies were included for extensive analyses.…”
Section: Methodsmentioning
confidence: 99%
“…; Kolgeci et al. ; Larsson & Wennerberg ). The hardware complications, however, will affect the clinical success of implant‐supported zirconia restorations.…”
mentioning
confidence: 98%